2016
DOI: 10.1021/acs.jafc.6b00380
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anthranilic Diamide Scaffolds Containing N-Substituted Phenylpyrazole as Potential Ryanodine Receptor Activators

Abstract: To discover potent insecticides targeting ryanodine receptors (RyRs), a series of novel anthranilic diamides analogues (12a-12u) containing N-substituted phenylpyrazole were designed and synthesized. These compounds were characterized by (1)H NMR, (13)C NMR, and HRMS, and the structure of compound 12u was confirmed by X-ray diffraction. Their insecticidal activities indicated that these compounds displayed moderate to excellent activities. In particular, 12i showed 100 and 37% larvicidal activities against ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Insecticidal activity against M. separata varied remarkably depending upon substituents (R ′ 3 and R ′ 4 ) on the benzene ring of the phenylpyrazole moiety. In general, when R 1 , R 2 , and R ′ 3 were fixed, the overall sequence of R ′ 4 related to the larvicidal activity of title compounds was Cl > CF 3 > H ≥ CH 3 The results indicated that all tested target compounds exhibited excellent insecticidal activity at the concentration of 5 mg L −1 . Moreover, it was noteworthy that some compounds, such as 6a, 6h, 6p, and 6r, had potent activity when compared with the standard chlorantraniliprole.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Insecticidal activity against M. separata varied remarkably depending upon substituents (R ′ 3 and R ′ 4 ) on the benzene ring of the phenylpyrazole moiety. In general, when R 1 , R 2 , and R ′ 3 were fixed, the overall sequence of R ′ 4 related to the larvicidal activity of title compounds was Cl > CF 3 > H ≥ CH 3 The results indicated that all tested target compounds exhibited excellent insecticidal activity at the concentration of 5 mg L −1 . Moreover, it was noteworthy that some compounds, such as 6a, 6h, 6p, and 6r, had potent activity when compared with the standard chlorantraniliprole.…”
Section: Resultsmentioning
confidence: 94%
“…Different substituted phenylhydrazines 1a–1c and compounds 4a–4f were prepared as described in the literature with some modifications as shown in Fig. .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The insecticidal activity of title compounds and rynaxypyr against oriental armyworm (Mythimna separata) was tested according to the leaf-dip method using the reported procedure at 600 mg/L dose [32].…”
Section: Larvicidal Activity Against Mythimna Separatamentioning
confidence: 99%